From Margins to Mainstream: Probing the Amazigh-in-Education Policy in Morocco - Laaguid, Brahim Ait (Journal of Digital Sociohumanities, 2025)
The teaching of Amazigh has been celebrated by plenty of activists as a cornerstone toward revitalizing the Amazigh language and culture. Grand efforts have been made to ameliorate both the process and product of this policy. However, several issues persist, raising questions about officials’ political will and the full engagement of educators, learners, and their families. The present paper delves into Moroccans’ attitudes and views on the Amazigh teaching experience. It adopts a qualitative approach, as data were collected using a questionnaire and analyzed through thematic analysis. Results show that Moroccans generally perceive the teaching of Amazigh as an essential step toward reconciliation with the Amazigh identity. The 21-year-long experience is, however, regarded by the majority of participants to be a fiasco for several reasons, including lack of resources and educational staff and the incessant insignificance and carelessness associated with Amazigh. Most of the respondents, nevertheless, strongly support the adoption of the Tifinagh script, suggesting that it is a requisite part of Moroccan history and culture. The future of the Amazigh language is yet held with great pessimism, especially due to the fierce competition of other languages. The study calls for working on changing Moroccans’ negative attitudes and beliefs on Amazigh, arguing that without a solid social foundation, neither activists’ militancy nor constant political changes would be of any value.